AB0081 Low lipocalin-2 in systemic lupus erythematosus pregnancies- a possible mechanism for loss of tolerance. (12th June 2018) - Pedersen, T.T.; Fenstad, M.H.; Jakobsen, B.; Koksvik, H.S.; Moksnes, T.S.; Wallenius, M.; Flo, T.H.; Haug, M.
Abstract : Background: Lipocalin-2 (LCN2) has become increasingly relevant as a potential clinical biomarker of rheumatic diseases. 1 The biological role of LCN2 in the adaptive immunity is less understood. It has been shown that LCN2 can induce immune tolerance by upregulation of human leukocyte antigen G (HLA-G) expression and by expansion of T-regulatory cells. 2 LCN2-deficient mice have been found to be more susceptible to induction of autoimmunity. 3 Systemic lupus erythematosus (SLE) is a disease associated with loss of tolerance. Pregnancy complications seen in SLE are also regarded as a consequence of immune dysregulation. LCN2 might therefore play a role as an immune modulator in SLE-pregnancies. Objectives: The study objective was to obtain a better understanding of immune regulation in pregnant women with SLE. In this study, we analysed serum LCN2 and clinical parameters in women with RA, SLE and healthy controls during pregnancy and postpartum. Methods: The Norwegian National Advisory Unit on Pregnancy and Rheumatic Diseases collects serum samples in a biobank from women with inflammatory rheumatic diseases. Samples were obtained before pregnancy, in each trimester and 6 weeks, 6 months and 12 months postpartum from pregnant women with SLE (n=28), RA (n=34) and healthy pregnant controls (n=19). A sandwich ELISA was used to measure LCN2 in the serum samples. The biobank database was linked to RevNatus, a Norwegian quality registry collecting comprehensive clinical data about these women. Results: Our cohort of pregnant women with SLE and RA had low disease activity throughout pregnancy and 67%–95% used medication (table 1). LCN2 levels in serum samples from women with SLE were found significantly lower compared to samples from women with RA and healthy controls at all time-points (p<0.05) (graph). Conclusions: Pregnant women with SLE had lower levels of LCN2 compared to pregnant women with RA and healthy controls. Our cohort of women had well controlled disease, making it likely that our findings represent inherent biological differences rather than effects of disease activity. Low LCN2 levels can be a possible mechanism for loss of tolerance seen in SLE patients during pregnancy. References: [1] Abella V. Biomarkers2015;20(8):565–71. [2] La Manna G. PLoS One2014Feb 27;9(2). [3] Pawar RD. Clin Immunol2014Sep;154(1):49–65. Acknowledgements: This study is supported by grants from St. Olavs Hospital and Norsk Revmatikerforbund. Disclosure of Interest: None declared